Evaluation of the Knowledge and Perceptions about Pharmacovigilance Activities among Pharmacy Students in Nigeria: A Cross-Sectional Study - Patrick, Osemene Kanayo; Olubunmi, Afolabi Margaret (Bangladesh Pharmaceutical Journal, 2017)
Studies on pharmacovigilance (PV) activities in Nigeria focused on perceptions of PV among professional healthcare workers are described here. There is paucity of information on pharmacy students knowledge about PV activities. Hence, this study, evaluated the knowledge and perceptions of final year pharmacy students about PV activities using descriptive and inferential statistics. A cross sectional study was undertaken in three Nigerian universities with a pretested questionnaire during the period of January and February, 2016. The questionnaire included closed-ended questions on demographic variables and questions designed to achieve the objectives of the study. Data was analyzed with IBM SPSS Statistics 20 and presented in percentages, means, standard deviations and median at 50% percentile. The mean knowledge score of pharmacovigilance and adverse drug reporting for the final year students was 4.25±0.18. There were significant differences in the mean scores of knowledge domain by age groups 21-24 years 4.8±0.70, 25-30 years 6.2 ± 0.84 and >30 years 4.6±0.72 at p=0.001; gender: male 4.1±1.20 and female 4.4±0.98 at (p=0.0001) as well as the current universities attended as follows University 1 with a scrore of 5.1±1.03, University 2 had a mean score of 6.3±0.99 at p=0.0120 and University 3 with a mean score of 4.3±1.01 at p=0.012. Furthermore, significant difference exist in the mean values of pharmacovigilance knowledge between those who had taking some courses in pharmacovigilance (7.3± 0.22) and those who did not (4.7 ± 0.13) at p=0.0001. Generally, the students had inadequate knowledge of PV activities. Therefore, emphasis on relevant PV courses in their curriculum is necessary. Bangladesh Pharmaceutical Journal 20(1): 1-13, 2017